FATORE
d)
![36 {a}^{2} b \: - 48a {b}^{2} 36 {a}^{2} b \: - 48a {b}^{2}](https://tex.z-dn.net/?f=36+%7Ba%7D%5E%7B2%7D+b+%5C%3A++-+48a+%7Bb%7D%5E%7B2%7D+)
e)
![(x - 1 {) \:}^{2} \: - 1 (x - 1 {) \:}^{2} \: - 1](https://tex.z-dn.net/?f=%28x+-+1++%7B%29+%5C%3A%7D%5E%7B2%7D++%5C%3A++-+1)
f)
![(x + 5 {) }^{2} - 9 (x + 5 {) }^{2} - 9](https://tex.z-dn.net/?f=%28x+%2B+5+%7B%29+%7D%5E%7B2%7D++-+9)
g)
![25 - (x + y {)}^{2} 25 - (x + y {)}^{2}](https://tex.z-dn.net/?f=25+-+%28x+%2B+y+%7B%29%7D%5E%7B2%7D+)
h)
![9 {a}^{2} - (a - 5 {)}^{2} 9 {a}^{2} - (a - 5 {)}^{2}](https://tex.z-dn.net/?f=9+%7Ba%7D%5E%7B2%7D++-+%28a+-+5+%7B%29%7D%5E%7B2%7D+)
Soluções para a tarefa
Respondido por
2
Resposta:
OLÁ
d) 36a²b-48ab²
12ab.(3a-4)
e)(x-1)²-1
usando
a²-b²=(a-b)(a+b)
(x-1-1).(x-1+1)
(x-1-1)x
(x-2)x
x.(x-2)
f) (x+5)²-9
usando
a²-b²=(a-b)(a+b)
(x+5-3).(x+5+3)
(x+2).(x+8)
g) 25-(x+y)
usando
a²-b²=(a-b)(a+b)
(5-(x+y)).(5x+(x+y))
(5-x-y).(5+x+y)
h) 9a²-(a-5)²
usando
a²-b²=(a-b)(a+b)
(3a-(a-5)).(3a+(a-5))
(3a-a+5).(3a+a-5)
(2a+5).(4a-5)
Explicação passo-a-passo:
espero ter ajudado
Perguntas interessantes
Matemática,
8 meses atrás
Química,
8 meses atrás
ENEM,
8 meses atrás
Química,
10 meses atrás
Matemática,
10 meses atrás
Física,
1 ano atrás
Inglês,
1 ano atrás